DĀDUŠA'S STELA AND THE VEXED QUESTION OF IDENTIFYING THE MAIN ACTORS ON THE RELIEF. (13th September 2017) - Rollinger, Robert
Abstract : This contribution deals with the famous stela of king Dāduša of Ešnunna ( c . eighteenth centuryb.c. ). The monument testifies to a correlation of text and image that is unique in the Ancient Near East. However, recent scholarship still disagrees on the identification of the three main actors in the top register of the stela. The paper discusses in detail the philological and epigraphic evidence and their larger contexts. It concludes that the slaying figure to the left standing on the defeated king of Qab(a)rā is Adad and the figure to the far right is the pious king of Ešnunna paying reverence to his god who guaranteed victory over his enemy.